Leakage Immune 9T-SRAM Cell in Sub-threshold Region - Gupta, Priya; Gupta, Anu; Asati, Abhijit (Bulletin of Electrical Engineering and Informatics, 2016)
The paper presents a variability-aware modified 9T SRAM cell. In comparison to 6T SRAM cell the proposedÂ  cell achieves 1.3Ã higher read-SNM and 1.77Ã higher write-SNM with 79.6% SINM (static current noise margin) distribution at the expense of 14.7Ã lower WTI (write trip current) at 0.4 V power supply voltage, while maintaining similar stability in hold mode. Thus, comparative analysis exhibits that the proposed design has a significant improvement, thereby achieving high cell stability at 45nm technology.